Immaginare la fine del mondo Adieu au langage di Jean-Luc Godard - Calabrò, Irene (Aesthetica Preprint, 2023)
The paper aims to investigate the relationship between imagination and 3D in Jean-Luc Godard’s Adieu au langage (2014). Through the analysis of film’s images and sequences, the objective of the paper is showing how Godard’s deconstruction of 3D is an attempt to reactive imagination as human faculty, practicing in an invisible space between images, that is fundamental to think and reinvent reality.